Rebalancing agricultural subsidies under the World Trade Organisation Agreement on Agriculture to attain food security in Africa - Maziwisa, Michelle (University of Pretoria, 2025)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2025.